INFLAMMATORY CYTOCINES GENES POLYMORPHISM ASSOCIATION WITH SERUM LEVELS OF BIOCHEMICAL MARKERS AT THE CORONARY ATHEROSCLEROSIS - A. V. Shevchenko; V. F. Prokofyev; Yu. I. Ragino; A. M. Chernjavski; M. I. Voevoda; V. I. Konenkov (Медицинская иммунология)
We have assumed, that serum production of biological markers that are significantly reflecting a risk degree for atherosclerotic process and acute coronary events may be modified by functional polymorphisms of a functional complex of genes that may be involved into inflammatory process and influence mutual regulation of their production. Therefore, we have assayed a number of appropriate gene polymorphisms and assessed frequency distribution for several promoter genotypes and their combinations, e.c., TNF-A863C; TNF-A308G; TNF-A238G; IL1B C-31T; IL1B-C511T; IL4-C590T; IL6-C174G; IL10A-1082G, IL10-А592C genes, regulatory sites of VEGF-А2578С, VEGF+Т936 gene variants. We have also measured serum levels of TNFα, IL-1β, IL-6, IL-8, IL-1 receptor antagonist (IL-1ra), C-reactive protein, soluble CD40 ligand receptor (sCD40L) in the patients with atherosclerosis. In general, it has been shown that contribution of single cytokine genotypes to the association with level of their production is much lower, than odds ratio of changed protein production associated with a compound genotype.